Morbidität und Mortalität der Hämo philie-Patienten in Deutschland - Schramm, W.; Rieger, A.; für teilnehmende Behandlungseinrichtungen (Hämostaseologie, 2012)
Since 1982 an annual multicentric survey regarding the epidemiology of patients suffering of haemophilia is performed with support of haemophilia treating centres of any size. Again, the actual compilation is resting upon a broad database returning to over 30 years of inquiry well representing both the actual and retrospective status of mortality. Prompted was exclusively information about patients with haemophilia A, B and von Willebrand disease. In particular anonymous data concerning the preceeding 12 months about number of treated patients, type and severity of illness, HIV-status and detailed information about causes of death was inquired. This data was merged with existing data and analysed statistically. In the 2009/2010 survey, a total number of 9448 patients with bleeding disorders have been reported from 47 participating centres. Despite mortality from HIV in patients with haemophilia is keeping on decreasing, HIV still remains an important factor as an HIV/HCV coinfection seems to increase risk of progression of severe liver disease. In the actual investigation the findings of the foundation “Humanitäre Hilfe für durch Blutpro-dukte HIV-infizierte Personen” were compared for the first time to our data. Time trends were visualised with a moving average. Our investigation has a smaller number of deceased patients, but contains consistent data.
Keywords: Haemophilia; haemophilia A; haemophilia B; von Willebrand disease; epidemiology; factor VIII; factor IX; morbidity; mortality; cause of death; HIV; AIDS; HCV